Affective dimensions and the psychosocial work performed by naked body protests. - Mathebula, Mpho (Social Movement Studies, 2025)
This paper is about the liberatory affective states associated with participation in naked body protests. The article will also touch on notions of gender as performative and located within the habitus, since affective states are intertwined with gender performance, embodiment and social construction. Exploration of these phenomena is done by analysing interview data from 16 women who participated in various naked body protests in South Africa. These include protests in Dobsonville, Soweto in 1990 and student protests at four universities in 2016. The study draws upon Wetherell's theorisation of affect, especially their concept of affective practice. The findings illustrate that affects are always embedded in acts and practices, including forms of protest. In addition, using Judith Butler's gender performativity theory, the study demonstrates that naked body protests have performative possibilities that both reify and challenge gender.